The Influence of Leadership, Cooperation, Welfare, and Work Ethic on Madrasah Educator Performance: The Role of Motivation and Competence - Bambang Sugeng; Muhammad Akmansyah; Idham Kholid; Oki Dermawan (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
Education is the key to progress and a challenge for every country, especially for developing countries like Indonesia. The problem of education quality in Indonesia can be seen from the low achievement of madrasahs and the results of the 2022 Program for International Student Assessment (PISA) evaluation. This research aims to explore the variables that influence the performance of educators in Bandar Lampung, with a focus on the leadership of madrasah heads, cooperation, welfare, motivation, personality competence, and work ethic of educators. This research uses a qualitative approach with exploratory and causal methods to identify and analyze the relationship between these variables. Data was collected through surveys and analyzed using multiple linear regression. The results of the research show that partially and simultaneously, the leadership of the madrasa head, cooperation, welfare, motivation, personality competence and work ethic have a significant effect on the performance of educators. Educator competency is the most dominant variable influencing educator performance. This research underlines the importance of good management of human resources in education to improve the quality of education. Recommendations are given to improve the performance of educators through improving leadership management, collaboration between educators, increasing welfare, motivation, as well as developing the competence and work ethic of educators.